Presidential address - Advances in bacterial blight of cotton - VERMA, J.P. (Indian Phytopathology, 2002)
Bacterial blight of cotton induced by Xanthomonas campestris pv. malvacearum (Xcm) was first recorded in Alabama (USA) in 1891, but in India it was reported in 1918 from Madras. Several epiphytotics occurred during 1948-1952, and the disease was well established in the 1960s in India, when a campaign was started to replace the rain-fed indigenous diploid cottons by high-yielding but susceptible tetraploid hirsutum and barbadense cottons. Irrigation and high nitrogenous fertilisers given to achieve yield potentials, also proved favourable for the disease development. In India, the disease is known to occur in all the cotton-growing areas with an annual losses varying from 5 per cent to 25 per cent. During this period, several cvs belonging to all thefour species were rejected (Verma and Singh, 1971a, 1974a) due to their high susceptibility to blight of cotton e.g., Karungani-1, Westerns, Cambodia, Madras, Uganda, 79-2, 458-1, Bar 12/1, 12/2, T-96, LL-54, LL-55, etc. Further, all the cvs grown in India were susceptible to the disease, which reduced the 'life' of a cv and it was considered essential (Verma and Singh, 1974b; Verma et al., 1980) to have, at least, tolerance to the disease before a cv was released for cultivation in any part of India.